Música de América : estudio preliminar y edición crítica - Wolkowicz, Vera; Biblioteca Nacional (Argentina) (Buenos Aires, Argentina : Teseo : Biblioteca Nacional, 2012)
Compilation of pieces originally published from 1920 to 1922 in the journal Música de América, with introductory essay and critical notes in Spanish.
Flor de cardo / José André -- Leyenda de la tarde / Aníbal Aracena Infanta -- Nostalgia llanera / Pablo M. Beruti -- La niñita regalona ; Préludio núm. 4 / Próspero Bisquertt -- Ariana y Dionysos. Segundo cuadro, Danza de Bacantes / Felipe Boero -- La Cruz del Sud / Alfonso Broqua -- Háblame / Alfredo Carrasco -- Humoreske / José María Castro -- Río indígena / Luis Cluzeau Mortet -- Suite, op. 7. Sarabanda / Joaquín Cortés López -- Regreso / Enrique de Herrera y Lerena -- A ti única / Pascual de Rogatis -- Giga / Víctor de Rubertis -- Ninna-Nanna / Domingo Dente -- Sarandí en la corriente / Eduardo Fabini -- Evangélica / Eduardo Fornarini -- El zorzal / Vicente Forte -- La abeja / José Gil -- Qué linda sois : vidala en tono mayor ; Bailecito ; Vidala : De lejas tierras ; Canto indígena ; Zamba ; El cuando / Manuel Gómez Carrillo -- Campera : al estilo popular / Carlos López Buchardo -- Preludio / Arturo Luzzatti -- Canción triste / Alberto Machado -- Canción del boyero / Juan Bautista Massa -- Ballet de marionnettes / Gabriel Palau -- En los Andes / Edmundo Pallemaerts -- La blanca rosa / Víctor A. Pasqués -- La chilota : cueca / Celerino Pereira -- Lejos de ti ; Las mañanitas / Manuel M. Ponce -- Las mariposas / Ricardo Rodríguez -- Romanza núm. 2 para piano / Franscisco Salgado -- Canción variada / Armando Schiuma -- Triste / César A. Stiattesi -- Beati mundo corde : motet a 3 voix mixtes / Celia Torrá -- El indiecito de Pichi-Mahuida / José Torre Bertucci -- Saika. Segundo cuadro, Un bosque encantado ; Bajo el parral / Floro M. Ugarte -- Ollanta. Acto 2. Dúo Yaraví ; Ollanta Yaraví. Piano solo / José María Valle-Riestra -- Canción serrana. Núm. 2 ; Canción serrana. Núm. (4) 3 / Alberto Villalba Muñoz -- A prole do bebê. 3, Caboclinha / Heitor Villa-Lobos -- Santos Vega bajo un sauce llorón : milonga ; Adiós a la tapera : milonga / Alberto Williams.
Includes bibliographical references.
Vocal texts in Spanish, Latin or Italian.
Online resource; title from ePub title page (Digitalia, viewed April 22, 2016)
Keywords: Nationalism in music; Vocal music -- Latin America; Piano music -- Latin America; Violin and piano music -- Latin America -- Scores; Piano music -- Scores; Vocal music -- Scores; Electronic books